Моніторинг сільськогосподарських земель в Україні: міф чи реальність? - Куссуль, Н.М. (Вісник НАН України, 2020)
Україна стоїть на порозі запровадження ринку землі, відкриття якого заплановане на 2020 р. Для забезпечення прозорості та надійності цього процесу потрібна достовірна інформація про реальне землекористування, його історію, стан сільськогосподарських культур у кожному сезоні та інші показники, які істотно впливають на ринкову вартість землі. Сьогодні в Україні немає відкритої системи з інформацією про реальне землекористування та власників земель, є лише державна кадастрова система, що містить певні помилки й неточності. Тому на часі створення правових, технічних і законодавчих передумов для відкриття ринку землі та розроблення геопросторової інформаційної системи реального землекористування в Україні. Саме на вирішення цих питань спрямована програма Світового банку «Підтримка прозорого землекористування в Україні», яка виконується за фінансової підтримки ЄС. Ukraine is on the verge of opening the land market. This process will begin in 2020, when free sale of land will be introduced. Currently, only the lease of the land is officially allowed. To ensure transparency, equity and reliability of this process, objective information on real land use and its history, crop development state in each vegetation season is required. All these indicators significantly affect the market value of the land. However, there is no publicly available system in Ukraine with information on real land use and landowners. This information is only contained in the state cadaster system, which contains a lot of incorrect information, since land ownership acts were generated chiefly manually. These mistakes became obvious after the process of digitizing the state cadaster. Therefore, creation of the legal, technical and legislative prerequisites for opening the land market becomes an extremely important task, as well as the development of geospatial information system of real land use in Ukraine. The World Bank program “Supporting Transparent Land Governance in Ukraine” with financial support from the EU is aimed at addressing these issues.